EXPERIMENTAL STUDY OF VERTICAL AXIS WIND TURBINE WITH PRE-SWIRL AUGMENTED - Riady, M. Ihsan; Santoso, Dyos; Ervega, Frandiaz Agustan (Indonesian Journal of Engineering and Science, 2024)
The paper presents an experimental investigation on a vertical axis wind turbine that utilizes pre-swirl augmentation through a concentric stator and rotor system. The study's main objective is to demonstrate that incorporating a stator as a guide blade can significantly enhance the turbine's performance. The rotor is positioned in the inner region of the turbine and is rotated by the flow induced by the stator surrounding it in the outer region. The stator accelerates the incoming wind before it reaches the rotor. The turbine has five rotor blades and has been tested with stator guide blades varying from zero to six and twelve. Both the guide rotor and blades use a modified cp-100-050-gn cambered plate airfoil. The tests were conducted at an average wind speed of 4 m/s. The results indicate that utilizing a stator with six guide blades leads to a 52% increase in the power coefficient, while a stator with 12 guide blades yields a slightly higher increase of 58%. Moreover, the turbine with a stator comprising 12 guide blades takes less time to attain maximum speed under no-load conditions than the one with a stator with six guide blades.